(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In this article, it is explained in detail that adolescence is a special period, that is, a period of transition, a complex period, a crisis period. In addition, the problems that arise in adolescents and their solutions are covered in detail.